PENDEKATAN TEKNIK KONSELING SELF DALAM MENGATASI KECANDUAN GAME ONLINE MELALUI LAYANAN KONSELING INDIVIDUAL DI SMP AL-HIDAYAH MEDAN - Cahya Eliza Dalimunthe (UIN Sumatera Utara, 2020)
The problem in this study is the condition of online game addiction experienced by students with research subjects Medan Al-Hidayah Middle School students. This study aims to determine the implementation of a self-counseling technique approach through individual counseling services for students who are addicted to online games at Al-Hidayah Middle School Medan. This study used a qualitative method with the subject of the research counseling guidance teacher and 6 students of Al-Hidayah Medan Middle School. This research gives meaning that through self-counseling technique approach with individual counseling services can find out how the factors that cause online gaming addiction either observed or experienced by students. The conclusion was proven through the results of observations and interviews obtained from 6 students and BK teachers. The result is students can provide an explanation of the level of use of playing online games that are out of bounds after being given approaches and services to students who show a better attitude towards the approaches and services that have been provided by the guidance and counseling teacher in overcoming online game addiction.Keywords: Self Counseling, Individual Counseling, Addiction to online games